Maybe He Just Likes You - Dee, Barbara (New York : Aladdin, 2019)
When boys in her class start touching seventh-grader Mila and making her feel uncomfortable, she does not want to tell her friends or mother until she reaches her breaking point.
Keywords: Sexual harassment -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Single-parent families -- Juvenile fiction; Families -- Juvenile fiction; Sexual harassment -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Single-parent families -- Fiction; Family life -- Fiction